(untitled) (Analysis in Theory and Applications, 2013)
The order of magnitude of multiple Fourier coefficients of complex valued functions of generalized bounded variations like (Λ^1,…, Λ^N)BV^(p) and r-BV, over [0, 2π]^N, are estimated.